THE CONTENT OF ORGANIC MATTER IN FODDER CEREAL GRASSES OF PRECARPATHIA - Karbivska, U. M. (Scientific Progress & Innovations, 2020)
Hay lands are sources of high quality and cheap fodders for livestock. Using fertilizers is one of the most effective measures to improve them. They change growth conditions of meadow grasses, which lead to the dominance of valuable species of cereal grasses. So, the research purpose was to find and investigate main factors of organic matter influence in fodder cereal grasses agro-phytocenosis of Precarpathia. The article presents research results of fertilizer effect on chemical composition and quality of cereal grass fodders. Seasonal, yearly changes in species composition and application of fertilizers influence chemical composi-tion and quality of fodder cereal grasses. The highest results in the studied grass mixtures (content of crude protein, metabolic energy, fodder units, and the highest amount of digested protein in fodder unit) was ob-served at application of nitrogen fertilizers in the dose of N75 and N150. It has been established that applying mineral fertilizers in the dose of N150P60K90 resulted in increasing the following indicators: crude protein content reached 16 %, crude protein –13.3 %, crude fat –3.7 %, crude fiber –28.5 %, and nitrogen free com-pounds–41.6 %. The content of calcium and magnesium crude ash also increased insignificantly under the impact of nitrogen fertilizers. At applying nitrogen fertilizers in the doze of N150, the nutritional value and energy intensity slightly increased, the content of fodder units increased from 72–73 % to 74–75 % (zoo-technical rate is within 80–90 %), metabolic energy per 1 kg of dry weight increased from 8.0–8.1 to 8.2–8.3 MJ/kg (zoo-technical rate is 8–9 MJ/kg) Mineral composition of these fodder cereal grasses meets zoo-technical standards of livestock fodders. Nitrogen fertilizers increased calcium content of plants as com-pared with the variants without fertilizers: N75 – from 0.41–0.43 to 0.46–0.47 %; N150 – 0.52–0.54 %. Calci-um to phosphorus ratio (Ca: P) changed after applying N75 from 1.1–1.2 to 1.3–1.4; N150 – to 1.5–1.7. Potas-sium to calcium (K: Ca) ratio and potassium to magnesium (K: Mg) decreased from 4.7–5.0 to 3.8–4.2, and to 3.1–3.3 respectively. The application of potassium and phosphorus fertilizers led to increasing their con-tent in grass mixtures. Potassium content in fodder dry mass increased by 0.16–0.25 % after K90 application as compared with control and fertilizer variants (N75, N150). Applying P60 resulted in increasing phosphorus content only by 0.03 % as compared with the variants without fertilizer and application of N90, N180. Calcium to phosphorus (Ca: P), potassium to calcium (K : Ca) and potassium to magnesium (K : Mg) ratios were within the zoo-technical norms.